2022
DOI: 10.3389/fphar.2022.800986
|View full text |Cite
|
Sign up to set email alerts
|

Pentagalloyl Glucose, a Major Compound in Mango Seed Kernel, Exhibits Distinct Gastroprotective Effects in Indomethacin-Induced Gastropathy in Rats via Modulating the NO/eNOS/iNOS Signaling Pathway

Abstract: Gastric ulcers are a common health disorder that affect up to 10% of the world’s population. The gastroprotective potential of pentagalloyl glucose (PGG) against indomethacin-induced ulcer in rats and the possible underlying mechanisms were investigated. Gastric ulceration was induced by indomethacin (single dose, 60 mg/kg). Pretreatment with PGG (100 or 200 mg/kg, orally) for 8 days prior to the administration of indomethacin furnished significant reductions in gastric mucosal lesions as well as a significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…LC-MS/MS analysis of C. coggygria ethanol extract in our previous study showed that the extract contained polyphenolic compounds such as ethyl gallate, ethyl ester of digallic acid, gallic acid, methyl gallate, myricetin, myricetinglucoside, myricetinrhamnoside, protocatechuic acid, quercetinrhamnoside, and quinic acid with pentagalloylglucose being the major compound [ 33 ]. The previous studies have shown that pentagalloylglucose had significant potential in the prevention of urolithiasis as well as strong antioxidant and anti-inflammatory activity [ 34 36 ]. Therefore, pentagalloylglucose along with other polyphenolic compounds in extract could be responsible for the preventive and curative effects of the extract against urolithiasis.…”
Section: Discussionmentioning
confidence: 99%
“…LC-MS/MS analysis of C. coggygria ethanol extract in our previous study showed that the extract contained polyphenolic compounds such as ethyl gallate, ethyl ester of digallic acid, gallic acid, methyl gallate, myricetin, myricetinglucoside, myricetinrhamnoside, protocatechuic acid, quercetinrhamnoside, and quinic acid with pentagalloylglucose being the major compound [ 33 ]. The previous studies have shown that pentagalloylglucose had significant potential in the prevention of urolithiasis as well as strong antioxidant and anti-inflammatory activity [ 34 36 ]. Therefore, pentagalloylglucose along with other polyphenolic compounds in extract could be responsible for the preventive and curative effects of the extract against urolithiasis.…”
Section: Discussionmentioning
confidence: 99%
“…Binding of PGG to a variety of targets has been investigated before via molecular docking, including using a SeamDock [ 31 ]. For example, molecular docking of PGG to two prostaglandin receptors was performed to understand its gastroprotective effects [ 33 ]. PGG was docked to the B-cell lymphoma 2 (bcl-2) family of anti-apoptotic targets (Bcl-2, BCL-XL, caspase 3, and caspase 9) with binding energies of −8.6, −7, −7.5, and 4.4 kcal/mol, respectively [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms by which PGG exerts its anticancer effects include an increase in oxidative stress, arresting the proliferation of abnormally growing cells at cell cycle checkpoints, enhanced autophagy and apoptosis of cancer cells, and inhibition of angiogenesis and metastasis. The potential therapeutic targets of PGG are transcription factors, namely STAT3 [ 40 , 45 , 61 ] and NF-κB [ 24 , 39 , 44 , 72 , 73 , 74 ], and growth factors, including vascular endothelial growth factor (VEGF; the primary target) [ 48 , 75 , 76 , 77 ]. PGG has anti-inflammatory activity, and its principal therapeutic targets are TNF-a [ 38 , 78 , 79 , 80 , 81 , 82 , 83 ], interferons [ 74 , 83 , 84 , 85 ], interleukins [ 78 , 80 , 82 , 83 , 84 , 85 , 86 ], and MCP-1 [ 79 , 80 , 87 ].…”
Section: Molecular Mechanisms Of Anticancer Effects Of Pggmentioning
confidence: 99%